Fast 3D isotropic imaging of the aortic vessel wall by application of 2D spatially selective excitation and a new way of inversion recovery for black blood imaging - Mooiweer, Ronald; Sbrizzi, Alessandro; El Aidi, Hamza; Eikendal, Anouk L.M.; Raaijmakers, Alexander; Visser, Fredy; van den Berg, Cornelis A.T.; Leiner, Tim; Luijten, Peter R.; Hoogduin, Hans (Magnetic resonance in medicine, 2016)
Purpose Aortic vessel wall imaging requires large coverage and a high spatial resolution, which makes it prohibitively time‐consuming for clinical use. This work explores the feasibility of imaging the descending aorta in acceptable scan time, using two‐dimensional (2D) spatially selective excitation and a new way of inversion recovery for black blood imaging. Methods The excitation pattern and field of view in a 3D gradient echo sequence are reduced in two dimensions, following the aorta's anisotropic geometry. Black blood contrast is obtained by partially inverting the blood's magnetization in the heart at the start of the cardiac cycle. Imaging is delayed until the inverted blood has filled the desired part of the aorta. The flip angle and delay are determined such that the blood signal is nulled upon arrival in the aorta. Results Experiments on eight volunteers showed that the descending aortic vessel wall could be imaged over more than 15 cm at a maximal resolution of 1.5 × 1.5 × 1.5 mm3 in less than 5 min minimal scan time. Conclusion This feasibility study demonstrates that time‐efficient isotropic imaging of the descending aorta is possible by using 2D spatially selective excitation for motion artifact reduction and a new way of inversion recovery for black blood imaging. Magn Reson Med 75:547–555, 2016. © 2015 Wiley Periodicals, Inc.